2023
DOI: 10.1101/gr.277628.122
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9-based repeat depletion for high-throughput genotyping of complex plant genomes

Abstract: High-throughput genotyping enables the large-scale analysis of genetic diversity in population genomics and genome-wide association studies that combine the genotypic and phenotypic characterization of large collections of accessions. Sequencing-based approaches for genotyping are progressively replacing traditional genotyping methods due to the lower ascertainment bias. However, genome-wide genotyping based on sequencing becomes expensive in species with large genomes and a high proportion of repetitive DNA. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In our study we used a pool of 6000 sgRNAs to perform target enrichment. Recently, depletion experiments were successfully done with a pool of ~ 500 000 sgRNAs in a single Cas9 digestion experiment (Rossato et al 2023).This indicates that the number of sgRNAs and therefore ROI can be signi cantly increased for guided-NOMe-seq as well.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we used a pool of 6000 sgRNAs to perform target enrichment. Recently, depletion experiments were successfully done with a pool of ~ 500 000 sgRNAs in a single Cas9 digestion experiment (Rossato et al 2023).This indicates that the number of sgRNAs and therefore ROI can be signi cantly increased for guided-NOMe-seq as well.…”
Section: Discussionmentioning
confidence: 99%
“…After cleavage, the plant’s (rice) 16S rRNA fragments are not amplified in the second PCR and are then excluded from the sequencing. In order to eliminate repetitive sequences from a genome that is particularly rich in repetitive elements, such as that of lentils, the target specificity of the CRISPR/Cas system combined with a set of over 500,000 gRNAs was used and allowed to exclude 40% of the reads mapping on repeats from sequencing and to enhance the number of reads mapping on unique regions by more than twice as much [ 104 ]. Using such methodologies allows us to focus on relevant genomic regions and to increase genotyping accuracy.…”
Section: Crispr/cas As An Enrichment Tool For Next-generation Sequencingmentioning
confidence: 99%
“…DASH works by cleaving target DNA in a sequencing library so that only non-targeted sequences with adapters at both ends remain to be sequenced. Rossato et al (2023) demonstrated the effectiveness of using the DASH method by using 566,766 sgRNAs to deplete repetitive elements in a lentil genome to improve genotyping methods. DASH-depletion resulted in a 37.7%-41.2% reduction of repetitive DNA sequences, with an increase of up to 160% in target DNA reads sequenced.…”
Section: Crispr-cas Mechanisms and Diversitymentioning
confidence: 99%
“…These methods both have relatively short lab protocols as the most timeconsuming step is a two-hour incubation. As with most initially expensive technologies, the cost of CRISPR-Cas assays can reduce dramatically when used in repeated monitoring (Rossato et al, 2023).…”
Section: In-field Detection Challenges and Solutionsmentioning
confidence: 99%